Bioaccumulation studies of heavy metal on impact towards polluted soil using earthworm Lampito mauritii and Eisenia fetida - Rameshkumar2, V.Prabakaran3, B. Govindarajan1*, M.Vigneeswaran1, G. (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Earthworms perform a number of essential functions in soil; the impacts of metals on earthworm are often investigated.Ã‚Â Present research showed the consideration towards the range of earthworm species (Lampito mauritii and Eisenia fetida), types of soil which was highly polluted with the deposits of match industry wastes and the other site has been contaminated by wastes from automobile service station. The discharge of effluent into the open land leads to pollution of soil surrounding the service station. Henceforth, the acronyms OS and MS are found in this paper, they refer to oil polluted soil (OS) and match industry soil (MS) Control soil (CS) was collected from the surface layer of mulberry garden field and forms of metal for metal uptake and accumulation. The bioaccumulation study was carried out by employing Lampito mauritii and Eisenia fetida as test animals to three different substrates viz., CS, MS and OS for 28 days. After the completion of exposure period, the heavy metal (Cd) concentrations in the earthworm body tissues were estimated Lampito mauritii, grown on MS, accumulated Cd in body tissue up to a level of 0.2610 mgkg-1, which was 6 times higher than those present at the beginning of the experiment. Similar trend was observed in another group of earthworms reared on OS. But the magnitude of Cr accumulation is only 9 times. It may be due to the high availability of this metal in the soil Similar experiment was carried out with Eisenia fetida on MS and OS. A significant accumulation was achieved by Eisenia fetida for the heavy metals Cd. When the experiment was started, the tissue concentrations of Cd in MS were 0.2484 mgkg-1 respectively. At the end of the experimental period, the tissue concentrations of this metal were 0.3095 mgkg-1 respectively. In the case of OS, similar trend was observed. Within 4 weeks, Cd increased drastically from 0.2484 mgkg-1 to 0.4502 mgkg-1.